Improving News Writing Skill by Using Cooperative Type Group Investigation Strategy - Putri, Delia (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2018)
This study aims to improve the skills of writing news on the student of Language and Literature Education Indonesia using strategy cooperatif type group investigation.This type of research is classroom action research with qualitative descriptive method. This research model refers to a model Kemmis and Mc Taggart. Subjects were students of Indonesian education enrolled in the academic year 2017/2018. Data collected by the test and non-test techniques. The instrument used, namely in the form of news writing test, interview and observation sheet. The results showed that an increase in news writing skills using strategy cooperatif type group investigation.This is evidenced from the average value of students in each cycle. The average value of 62.12 students in prasiklus then increased in the first cycle to 66.24 and the second cycle the average value of students increased to 87.00.